Food : The Chemistry of Its Components - Coultate, Tom (Royal Society of Chemistry)
Contenido: 1) Introducción; 2) Azúcares; 3) Polisacáridos; 4) Lípidos; 5) Proteínas; 6) Colores; 7) Sabores; 8) Vitaminas; 9) Preservadores; 10) Indeseables; 11) Minerales; 12) Agua.